2021
DOI: 10.1088/1748-0221/16/08/p08067
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of a NaIL detector for neutron/gamma discrimination

Abstract: NaI(Tl+Li) (NaIL) is a promising new inorganic scintillator for thermal neutron detection with the ability for pulse shape discrimination (PSD). In this study, we first built a dual-gamma/neutron sensitive detector based on a NaIL scintillator, a photomultiplier tube and a custom-built circuit. Then, we investigated its temperature response and optimized the PSD parameters, obtaining a figure of merit (FOM) of up to 4.5 at 0–50°C. Also, we examined the effect of the count rate on the detector's neutron and gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Studies have shown that the light yield of a NaIL scintillator changes under different temperatures [9,16], and the SiPM gain also changes with temperature [20,21]. Therefore, the output signal amplitude of the neutron-gamma detector designed in this study will change with temperature, which will cause a drift in the measured energy spectrum and measurement errors.…”
Section: Test Of Temperature Feedback Bias Correctionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that the light yield of a NaIL scintillator changes under different temperatures [9,16], and the SiPM gain also changes with temperature [20,21]. Therefore, the output signal amplitude of the neutron-gamma detector designed in this study will change with temperature, which will cause a drift in the measured energy spectrum and measurement errors.…”
Section: Test Of Temperature Feedback Bias Correctionmentioning
confidence: 96%
“…There have been some studies on NaIL scintillator-based neutron-gamma detectors. Most of the current research is based on the photomultiplier tube-coupled NaIL scintillator [8][9][10]. However, photomultiplier tubes are bulky, have high operating voltages, and are susceptible to interference.…”
Section: Introductionmentioning
confidence: 99%
“…where 𝜏 𝑓 is the fast component decay time constant, 𝜏 𝑠 is the slow component decay time constant, and 𝐴 and 𝐵 are the intensity coefficients of the two components, respectively. Studies have shown that the fast component usually dominates the pulses of NaIL scintillators [22,23], and the decay time constant of event pulses can be used to optimize frequency domain discrimination. According to Saleh's report [14], the optimal discriminating frequency can be obtained from eq.…”
Section: Length Of Pulse Transformationmentioning
confidence: 99%